Sistem tata kelola pemerintahan nagari dalam menciptakan public value di Nagari Sungai Nyalo IV Koto Mudiek, Kecamatan Batang Kapas, Kabupaten Pesisir Selatan, Sumatera Barat - Annisa Aulia Putri; Ria Ariany; Syamsurizaldi Syamsurizaldi (Publisia: Jurnal Ilmu Administrasi Publik, 2019)
Nagari Sungai Nyalo is one of the Nagari that applies the principles of governance to be able to advance the development of Nagari, and the welfare of the Nagari community. So, the community will be encouraged to participate in the governance process in Nagari. This research is aim to describe Local Governance Achievers in Sungai Nyalo IV Koto Mudiek Village, Batang Kapas District, Pesisir Selatan Regency. The research method used is qualitative with interview and documentation data collection techniques. Descriptive research type. The results showed that even though Nagari Sungai Nyalo IV Koto Mudiek won the Nagari Achievement competition, however, Governance was still not very good. This can be seen from (1) Accountability, the Government of Nagari Sungai Nyalo IV Koto Mudiek has interacted with the community at the decision making stage, but the socialization of the decision is still lacking (2) Transparency, the Government of Nagari Sungai Nyalo has been transparent, but still lacking in the absence of a website Nagari, and financial disclosure are still lacking (3) Participation, Community and Government have interacted well to increase community participation in the implementation of the Nagari Government.DOI: https://doi.org/10.26905/pjiap.v4i1.2432